Long-term efficacy and safety of fingolimod in Japanese patients with relapsing multiple sclerosis: 3-year results of the phase 2 extension study. Issue 1 (December 2017) - Saida, Takahiko; Itoyama, Yasuto; Kikuchi, Seiji; Hao, Qi; Kurosawa, Takayoshi; Ueda, Kengo; Auberson, Lixin; Tsumiyama, Isao; Nagato, Kazuo; Kira, Jun-ichi
Abstract Background The low level of disease activity and manageable safety profile seen with fingolimod versus placebo in a 6-month, phase 2, randomized controlled trial in Japanese patients with relapsing multiple sclerosis (MS; ClinicalTrials.gov Identifier NCT00537082) were maintained in the initial 6-month observational study extension. Here, we report long-term safety and efficacy results of the 3-year follow-up to the phase 2 study extension. Methods The 6-month core study was completed by 147 patients, of whom 143 entered the extension and took at least one dose of fingolimod. Those originally randomized to placebo were re-randomized to fingolimod 1.25 mg (n  = 23) or 0.5 mg (n  = 27). During the extension, the patients taking fingolimod 1.25 mg (n  = 46) were switched to open-label fingolimod 0.5 mg, and those originally randomized to fingolimod 0.5 mg (n  = 47) continued with open-label fingolimod 0.5 mg. Results Continuous fingolimod treatment was associated with a sustained low level of MRI and relapse activity for the duration of the extension phase; 75–100% (range across all assessment time points up to end of study) of patients remained free of Gd-enhanced T1 lesions, 88–100% remained free of new/newly enlarged T2 lesions, and 45–62% remained relapse-free. In patients who switched to the active treatment, a 79.5% decrease in annualized relapse rate (ARR; from 1.131 before switch to 0.232 6-months after switch) was observed in the first 6 months of the extension phase and thereafter remained low until the end of study (0.16–0.31 across all assessment time points after switch up to end of study). The mean number of Gd-enhanced T1 and new/newly enlarged T2 lesions decreased up to month 9 and thereafter remained low until the end of study (0.0–0.1 and 0.0–0.3, respectively, across all assessment time points after switch up to end of study). Fingolimod was generally well-tolerated and the safety profile was consistent with the core and 6-month extension. Serious adverse events were reported in 13.3% of patients during the extension study, with the range in the continuous fingolimod and placebo-fingolimod switch groups (3.7–21.7%) being similar to that reported in the core study for the placebo and fingolimod groups (5.3–20.4%). Conclusion Continuous fingolimod treatment over 36 months was associated with maintained efficacy and a manageable safety profile with no new safety signals. These results indicate that fingolimod provides long-term treatment benefit for Japanese patients with relapsing MS. Trial registration ClinicalTrials.govNCT00670449 (April 28, 2008).